2007
DOI: 10.1088/1742-6596/76/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

ZnO film for application in surface acoustic wave device

Abstract: High quality, c-axis oriented zinc oxide (ZnO) thin films were grown on silicon substrate using RF magnetron sputtering. Surface acoustic wave (SAW) devices were fabricated with different thickness of ZnO ranging from 1.2 to 5.5 µm and the frequency responses were characterized using a network analyzer. Thick ZnO films produce the strongest transmission and reflection signals from the SAW devices. The SAW propagation velocity is also strongly dependent on ZnO film thickness. The performance of the ZnO SAW devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…[1][2][3][4][5][6]. Of late, it has also been reported as a ferromagnetic material with a Curie point above room temperature either due to the presence of defects or with doping of Mn, Co or Ni [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]. Of late, it has also been reported as a ferromagnetic material with a Curie point above room temperature either due to the presence of defects or with doping of Mn, Co or Ni [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to widely used indium tin oxide (ITO) film, zinc oxide (ZnO) films have attracted considerable interest as a transparent conducting electrode [1]. Because of its direct band gap of 3.37 eV [2] and large exciton binding energy of 6 meV [3], ZnO thin film has a great potential in various area including gas sensor [4], light emitting diodes and UV lasers [5] and surface acoustic wave devices [6]. Many recent investigations have indicated that the electrical properties of the ZnO films may be modified by doping with Al, In and Ga [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO-based structures have been applied in a variety of fields such as light emitting diodes, photo diodes [4], solar cells [5,6], gas sensor [7], surface acoustic wave devices [8], field effect transistor [9] and piezoelectric devices [10].…”
Section: Introductionmentioning
confidence: 99%